2021
DOI: 10.1007/s00894-021-04923-w
|View full text |Cite
|
Sign up to set email alerts
|

Repurposing drug molecule against SARS-Cov-2 (COVID-19) through molecular docking and dynamics: a quick approach to pick FDA-approved drugs

Abstract: Graphical abstract A novel coronavirus known as severe acute respiratory syndrome is rapidly spreading worldwide. The international health authorities are putting all their efforts on quick diagnosis and placing the patients in quarantine. Although different vaccines have come for quick use as prophylactics, drug repurposing seems to be of paramount importance because of inefficient therapeutic options and clinical trial limitations. Here, we used structure-based drug designing approach to find and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…This was followed by Cys145 and His163 [38] as we also can observe in the riboflavin interaction residues. In addition, Gly143 and Glu166 reported playing an important role in stabilizing the ligand-receptor complex [39].…”
Section: Resultsmentioning
confidence: 99%
“…This was followed by Cys145 and His163 [38] as we also can observe in the riboflavin interaction residues. In addition, Gly143 and Glu166 reported playing an important role in stabilizing the ligand-receptor complex [39].…”
Section: Resultsmentioning
confidence: 99%
“…The 3D structures of the ligands {LOCM and those of the reference standard (zafirlukast [ 16 ], cefoperazone [ 17 ]), were obtained from PubChem “ (accessed on 15 January 2022)” and subsequently optimized via the addition of Gasteiger charges on UCSF chimera software V1.14 [ 18 ] in preparation for docking. Zafirlukast cefoperazone are good, repurposed drug candidates for COVID-19 targeting SARS-CoV-2 SP [ 16 , 17 ] and hence their selection as the reference standards in this study.…”
Section: Methodsmentioning
confidence: 99%
“…But in our study, the favipiravir is ineffective even at higher concentrations, the specific reasons need to be further explored. As for the antiviral candidates we found in this research, diosmin and cyanidin-3-O-glucoside were identified as inhibitor of SARS-CoV-2, since diosmin could bind covalently to the SARS-CoV-2 main protease, inhibiting the infection pathway of SARS-CoV-2 (44), and cyanidin-3-O-glucoside was demonstrated to inhibit M protein activity of SARS-CoV-2 in a dose-dependent manner at biologically relevant (μM) concentrations (45). The other three compounds, clinodiside A, secoxyloganin and disogluside, have not been reported to have antiviral effects yet.…”
Section: Discusssionmentioning
confidence: 99%